Administrative corruption from sociology perspective and the relationship between administrative corruption and social security - Zarei Jlyany, Mohsen; Sharafi, Gholam Reza; Tavani, Mustafa; Haghighatian, Mansour; Tavani, Moslem (Pure and Applied Science Advances, 2014)
certain principles Observance and non- Observance on organizing a social system will have Indisputable effect at the Organization. And administrative systems are not exempt from this, also the selection of the Administration components and also How to Place the components together can affect its performance. Meanwhile, the government's role in the prevalence or no-prevalence, the extent type and the way of administrative corruption influence, in this article, researchers wants to explore the reasonable cause of this procedure prevalence. So Thought owners by thinking more in this context, compensate Analysis deficiencies. Also following topics are included in this article, first of all. A) Administrative corruption and social security definitions B) Impact of administrative corruption on Social Security In terms of rational - traditional C) the most important point of Sociological Analysis And sociological theories relation with administrative corruption And relate these theories to deviations And its role in administrative corruption cases have been investigated.